Efficacy and safety of aspirin as an adjunctive therapy in tubercular meningitis: A systematic review and meta-analysis. (April 2021) - Rohilla, R.; Shafiq, N.; Malhotra, S.
Abstract: Background: Tubercular meningitis (TBM) is associated with high mortality and stroke with chronic neurological sequelae even with best of care and antitubercular therapy. Studies have shown that aspirin as an adjunctive therapy might play some role in management of TBM. This systematic review and meta-analysis has been planned to evaluate the efficacy and safety of aspirin as an adjunctive therapy in TBM patients. Methods: We conducted a systematic search of randomized controlled trials in patients with tubercular meningitis published till October 2019 in all major clinical journals. Study was registered with PROSPERO with registration number: CRD42019136689. Articles were tested for eligibility and assessed for quality and various bias. Data synthesis and analysis was done using Review manager 5.3. The primary end point for assessment of efficacy was mortality at three months. The secondary end point was stroke or composite outcome of stroke and mortality at three months. Adverse effects were also assessed as secondary safety end point. Findings: Overall, three eligible randomized controlled trials with 365 participants were included that provided quantitative data for this meta-analysis. The analysis of primary and secondary end points was done using fixed effect model. There was not significant reduction in mortality [hazard ratio 0.78 (95% CI 0.45–1.35, p  = 0.37)] and composite outcome of mortality and new onset stroke [hazard ratio 0.86 (95% CI 0.60–1.24, p  = 0.43)] in aspirin group as compared to placebo. However, aspirin as compared to placebo significantly reduced new onset stroke [hazard ratio of 0.51 (95% CI 0.29–0.87, p  = 0.01)]. Interpretation: We did not find significant reduction in mortality and composite outcome (mortality and new onset stroke) with aspirin as compared to placebo but there was significant reduction in new onset stroke in aspirin group as compared to placebo with Number Needed to Treat (NNT) = 10, which might be of clinical importance since stroke is responsible for high mortality and morbidity in these subset of patients. However, a large well conducted randomized controlled trial is required to put more light on the available evidence.